Evaluating mental health literacy and help-seeking behaviours in UK university students: a country wide study. Issue 4 (6th April 2020) - Gorczynski, Paul; Sims-Schouten, Wendy; Wilson, Clare
Abstract : Purpose: Despite a high prevalence of mental health problems, few students know where to turn for support. The purpose of this study was to gain a UK wide perspective on levels of mental health literacy amongst university students and to examine the relationship between mental health literacy and mental health help-seeking behaviours. Design/methodology/approach: A total of 300 university students in the UK participated in this online cross-sectional study. Participants filled out the mental health literacy scale, the general help-seeking questionnaire, Kessler psychological distress scale 10, The Warwick-Edinburgh mental well-being scale and the self-compassion scale: short form. Findings: Overall, 78 per cent of participants indicated mild or more severe symptoms of distress. Students reported lower levels of mental health literacy when compared to students in other nations. Women, bisexuals, and those with a history of mental disorders indicated high levels of mental health literacy. Participants indicated they were most likely to seek support from intimate partners and least likely to seek support from religious leaders. No significant correlations were found between mental health literacy and help-seeking behaviours. Mental health literacy was not correlated with distress, mental well-being or self-compassion. Help-seeking behaviours were only significantly positively correlated with mental well-being. Originality/value: Universities should address strategies to improve help-seeking behaviours in an effort to address overall mental well-being. Programmes may wish to help provide students with information about accessing face-to-face support systems. Environmental strategies to foster mental well-being on campus should also be explored.